Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/01.mib.0000438430.15553.90
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Restores the Dysfunctional Matrix Remodeling Protein and Growth Factor Gene Expression in Patients with Inflammatory Bowel Disease

Abstract: Our data suggest that suppression of inflammation results in the arrest of epithelial damage and subsequent mucosal healing. Therefore, the therapeutic potential of agents targeting MMPs or growth factors as primary therapy seems rather complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 40 publications
6
32
0
Order By: Relevance
“…Arjis et al showed restoration of abberant mucosal function by infliximab. 33 The ability to potentially quantitate mucosal disturbance would allow for evaluation of all patients with quantitative measurements, and as mucosal healing is now an established important endpoint, using a “treat-to-target” paradigm, biopsy procurement is very feasible. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Arjis et al showed restoration of abberant mucosal function by infliximab. 33 The ability to potentially quantitate mucosal disturbance would allow for evaluation of all patients with quantitative measurements, and as mucosal healing is now an established important endpoint, using a “treat-to-target” paradigm, biopsy procurement is very feasible. 34 …”
Section: Discussionmentioning
confidence: 99%
“…2 ADAMDEC1, first identified in 1997, is the sole member of a subsidiary class of the ADAM family. 1 It has been linked to a number of inflammatory diseases including atherosclerosis, 3 pulmonary sarcoidosis, 4 osteoarthritis, 5,6 Crohn’s disease, 7,8 and to gastrointestinal [GI] malignancies–gastric adenocarcinoma 9, 10 and colorectal cancer. 11, 12 The physiological role of ADAMDEC1 remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…34 Of note, one of the mechanisms by which infliximab, an anti-TNF-a monoclonal antibody, may reduce inflammation in human inflammatory bowel disease is through reduction in MMP levels. 35 The same molecular mechanisms apply in the case of wound healing in ulcer disease. The action of sucralfate goes beyond simply supplementing the mucosal barrier of the gastric epithelium and includes stabilizing acid and base (a and b)-FGF and preventing their degradation.…”
Section: Other Small Moleculesmentioning
confidence: 95%